DETECTION OF THE PVL GENE AMONG STAPHYLOCOCCUS AUREUS ISOLATES FROM PATIENTS WITH SKIN AND SOFT TISSUE INFECTIONS AND ITS ASSOCIATION WITH DISEASE SEVERITY (European Science Methodical Journal, 2026)
Background: Staphylococcus aureus is a major cause of skin and soft tissue infections (SSTIs). It remains unknown if Panton–Valentine leukocidin (PVL) and its virulence factors contribute to more severe diseases. Aim: To establish the prevalence of the pvl gene of Staphylococcus aureus among SSTI isolates and assess the association with disease severity. Materials and Methods: A cross-sectional study was conducted in Baghdad between December 2024 and January 2026 involving 71 patients with suspected SSTIs. Standard microbiological methods were used to identify the bacteria, and the VITEK 2 system confirmed the results. We evaluated 41 S. aureus isolates in total. Real-time PCR was used to find the pvl gene, and statistical analysis was used to see how it was related to the severity of the disease. Results: The pvl gene was detected in 24 (58.5%) isolates. A significant association was found between pvl positivity and increased disease severity (p = 0.032), with moderate and severe infections more common among PVL-positive cases. However, correlation analysis showed only a weak relationship. White blood cell counts were higher in moderate and severe cases but were not statistically significant. Conclusion: PVL-positive Staphylococcus aureus strains are prevalent among SSTI patients in Baghdad and may contribute to more severe infections, although disease severity remains multifactorial.